A statistical piston ring lubrication model considering the tribofilm and its effect of two-stroke marine engines. (January 2023) - Xiuyi, Lyu; Jiao, Bowen; Lu, Xiqun; Zou, Dequan; Ma, Xuan; Neville, Anne
Abstract: Statistical models are widely applied to marine engine simulation since the advantages of fast, efficient, and macroscopic fault. It is reported that there would be a boundary lubrication regime where the tribofilm could grow under the working condition of two-stroke marine engines. So far, there is no statistical lubrication model for two-stroke marine engines that could predict the tribofilm growth and evaluate its effect on the piston ring cylinder liner (PRCL) system. In this study, a tribofilm growth and wear model is attached to the piston ring lubrication model for obtaining the tribofilm thickness. Afterward, the coupled functional relationship between the tribofilm thickness and the comprehensive roughness is established with the help of the surface wear. Then, experimental results are employed to verify the correctness of this model. Finally, some essential simulation results, including the rate of tribofilm growth and wear, oil film thickness, and friction, could be obtained to reveal the importance of tribofilm in the lubrication performance of two-stroke marine engines. Highlights: This paper applied the tribofilm growth and wear model to marine engines in a statistical modeling way. The tribofilm dynamic growth process during the marine engines operation is predicted. This paper links tribofilm thickness and the comprehensive roughness of the piston ring and the liner. Therefore, this study could evaluate the effect of tribofilm on the lubrication model's essential input, the roughness.